(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
Our work explores the scope of wisdom as a central paradigm in the work of Gastón Soublette, proposing its link with the consecutive paradigms of people and humanity. Starting from the author’s express interest in wisdom as a horizon differentiated from academic philosophy, our research advances towards an elucidation of wisdom in Soublette as an improper, transhistorical question essentially determined by nature. Highlighting respectively the “sense” and the “law of analogy” as the object and strategy of wisdom, our work delves into the relationships between wisdom and indigenous and popular cultures as a manifestations of plain humanity. In this way, the problem of an archetypology of the human opens up, illuminated by Soublette through the figure of Christ and the wise men of prehistoric China.